Endometrial stromal sarcoma: A review of rare mesenchymal uterine neoplasm. Issue 11 (23rd August 2020) - Capozzi, V.A.; Monfardini, L.; Ceni, V.; Cianciolo, A.; Butera, D.; Gaiano, M.; Berretta, R.
Abstract: Objective: This review aims to analyze the pathological aspects, diagnosis and treatment of rare mesenchymal uterine tumors. Methods: On August 2019, a systematic review of the literature was done on Pubmed, MEDLINE, Scopus, and Google Scholar search engines. The systematic review was carried out in agreement with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyzes statement (PRISMA). The following words and key phrases have been searched: "endometrial stromal sarcoma", "low‐grade endometrial stromal sarcoma", "high‐grade endometrial stromal sarcoma", "uterine sarcoma", "mesenchymal uterine tumors" and "uterine stromal sarcoma". Across these platforms and research studies, five main aspects were analyzed: the biological characteristics of the neoplasms, the number of cases, the different therapeutic approaches used, the follow‐up and the oncological outcomes. Results: Of the 94 studies initially identified, 55 were chosen selecting articles focusing on endometrial stromal sarcoma. Of these fifty‐five studies, 46 were retrospective in design, 7 were reviews and 2 randomized phases III trials. Conclusion: Endometrial stromal sarcomas are rare mesenchymal uterine neoplasms and surgery represents the standard treatment. For uterus‐limited disease, the remove en bloc with an intact resection of the tumor (without the use of morcellation) is strongly recommended. For advanced‐stage disease, the standard surgical treatment is adequate cytoreduction with metastatectomy. Pelvic and para‐aortic lymphadenectomy is not recommended in patients with Low‐grade Endometrial Stromal Sarcoma (ESS), while is not clear whether cytoreduction of advanced tumors improves patient survival in High‐grade ESS. Administration of adjuvant radiotherapy or chemotherapy is not routinely used and its role is still debated.